Analysis of the Effect of Macroeconomic Variables and External Debt on Indonesia's Economic Growth for the First Quarter 2010- First Quarter 2020 - Cindy Fredlina; Ella Silvana Ginting; Apren Halomoan Hutasoit (Institute of Computer Science (IOCS), 2021)
This study aims to determine and analyze the Effect of Net Exports, Exchange Rates, Investment, Household Consumption and External Debt on Indonesia's Economic Growth for the period I quarter 2010 – first quarter 2020. The type of research used in this study is quantitative method. The type of data used in this study is secondary data obtained from the website of the Central Statistics Agency and Bank Indonesia. Based on the results of the classical assumption test on the independent variables of net exports, exchange rates, investment, household consumption and foreign debt, they do not pass the multicollinearity test. Therefore, the method to pass the multicollinearity test is to exclude several independent variables, namely household consumption and debt variables. overseas, so that the independent variables used in this study are net exports, exchange rates, and investment. The results of this research show that simultaneously net exports, exchange rates and investment have a significant effect on economic growth. Partially, the exchange rate has a significant effect on economic growth, while net exports and investment have no effect on economic growth.